Disrupting school spaces to enhance mathematics teaching and learning - Jojo, Zingiswa; Madikizela-Madiya, Nomanesi (Journal on Mathematics Education, 2022)
This paper is based on an argument that the disruption of school spaces can demerit the myth that Mathematics is difficult and a struggle for learners in some contexts. Combining spatial theories and the phenomenon of disruption, the paper reports from a qualitative research project that analyzed the dynamics of space and place in South African schools. From a sample of two secondary schools and three primary schools in Tshwane South, the paper reports on the data from one school where the theme of disruption of school spaces for the teaching of mathematics was drawn. Two Mathematics teachers and one Head of Department (HoD) were interviewed in the school and one classroom was observed. The findings indicate that the disruption of school spaces leads to collaboration across post levels in terms of teaching, management, and personal professional development. Such collaboration disrupts the representations of space and improves teachers’ spatial practices and a potential for better learning. The paper concludes by recommending research that will explore the applicability of the conclusions it makes to the enhancement of Mathematics learners’ results.